Priming Dental Pulp Stem Cells With Fibroblast Growth Factor‐2 Increases Angiogenesis of Implanted Tissue‐Engineered Constructs Through Hepatocyte Growth Factor and Vascular Endothelial Growth Factor Secretion. (21st January 2016) - Gorin, Caroline; Rochefort, Gael Y.; Bascetin, Rumeyza; Ying, Hanru; Lesieur, Julie; Sadoine, Jérémy; Beckouche, Nathan; Berndt, Sarah; Novais, Anita; Lesage, Matthieu; Hosten, Benoit; Vercellino, Laetitia; et al.
Abstract : Tissue engineering strategies based on implanting cellularized biomaterials are promising therapeutic approaches for the reconstruction of large tissue defects. A major hurdle for the reliable establishment of such therapeutic approaches is the lack of rapid blood perfusion of the tissue construct to provide oxygen and nutrients. Numerous sources of mesenchymal stem cells (MSCs) displaying angiogenic potential have been characterized in the past years, including the adult dental pulp. Establishment of efficient strategies for improving angiogenesis in tissue constructs is nevertheless still an important challenge. Hypoxia was proposed as a priming treatment owing to its capacity to enhance the angiogenic potential of stem cells through vascular endothelial growth factor (VEGF) release. The present study aimed to characterize additional key factors regulating the angiogenic capacity of such MSCs, namely, dental pulp stem cells derived from deciduous teeth (SHED). We identified fibroblast growth factor‐2 (FGF‐2) as a potent inducer of the release of VEGF and hepatocyte growth factor (HGF) by SHED. We found that FGF‐2 limited hypoxia‐induced downregulation of HGF release. Using three‐dimensional culture models of angiogenesis, we demonstrated that VEGF and HGF were both responsible for the high angiogenic potential of SHED through direct targeting of endothelial cells. In addition, FGF‐2 treatment increased the fraction of Stro‐1+/CD146+ progenitor cells. We then applied in vitro FGF‐2 priming to SHED before encapsulation in hydrogels and in vivo subcutaneous implantation. Our results showed that FGF‐2 priming is more efficient than hypoxia at increasing SHED‐induced vascularization compared with nonprimed controls. Altogether, these data demonstrate that FGF‐2 priming enhances the angiogenic potential of SHED through the secretion of both HGF and VEGF. Significance: The results from the present study show that fibroblast growth factor‐2 (FGF‐2) priming is more efficient than hypoxia at increasing dental pulp stem cells derived from deciduous teeth (SHED)‐induced vascularization compared with nonprimed controls. Together, these data demonstrate that FGF‐2 priming enhances the angiogenic potential of SHED through the secretion of both hepatocyte growth factor and vascular endothelial growth factor. Abstract : Tissue engineering strategies using implantation of cellularized biomaterials are promising approaches for large tissue defect reconstruction. Additional key factors regulating the angiogenic capacity of dental pulp stem cells derived from deciduous teeth (SHED) were characterized. The presented data demonstrate that fibroblast growth factor‐2 priming enhances the angiogenic potential of SHED through the secretion of hepatocyte growth factor and vascular endothelial growth factor.